2012
DOI: 10.1161/circep.111.967497
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Long-Term Follow-Up of Silent Cerebral Lesions After Pulmonary Vein Isolation Using a Remote Robotic Navigation System as Compared With Manual Ablation

Abstract: Background— The incidence of silent cerebral lesions (SCL) after atrial fibrillation (AF) ablation is highly variable, depending on the technology used. Recently, an increased risk for SCL has been described for a novel, nonirrigated ablation tool using multielectrode phased radiofrequency (PVAC). The aim of this prospective study was to evaluate the incidence and long-term follow-up of SCL in patients undergoing robotically assisted pulmonary vein isolation (RA-PVI) as compared with manual PVI. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(69 citation statements)
references
References 23 publications
2
67
0
Order By: Relevance
“…10 Recent reports have described a high prevalence of asymptomatic cerebral lesions after AF ablation procedures observed on diffusion-weighted MRI (DWI) that are presumed to be embolic in origin. [11][12][13][14][15][16] However, the exact mechanism and composition of the embolic material have not been characterized. The present study created an experimental model of left atrial ablation in swine to fully characterize and quantify the production of microbubble and particulate emboli to determine its potential for creation of asymptomatic cerebral ischemic lesions.…”
mentioning
confidence: 99%
“…10 Recent reports have described a high prevalence of asymptomatic cerebral lesions after AF ablation procedures observed on diffusion-weighted MRI (DWI) that are presumed to be embolic in origin. [11][12][13][14][15][16] However, the exact mechanism and composition of the embolic material have not been characterized. The present study created an experimental model of left atrial ablation in swine to fully characterize and quantify the production of microbubble and particulate emboli to determine its potential for creation of asymptomatic cerebral ischemic lesions.…”
mentioning
confidence: 99%
“…3,6,7,[15][16][17][18][19][20] Two studies also suggested that the rate of ACE associated with MER circular catheters was significantly higher than the ACE rate associated with irrigated RF catheters. 7,8 These 2 studies used an ACT cutoff of 300 seconds but used interrupted VKA with low-molecular-weight heparin bridging periablation.…”
Section: Incidence and Predictors Of Acementioning
confidence: 99%
“…Pre-existing lesions were predominantly found in the frontal and parietal lobes, as demonstrated in this sample patient. There were a median of 8 lesions per subject (interquartile range, [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. spontaneous; 45% were electrical).…”
Section: Procedural Parametersmentioning
confidence: 99%
See 2 more Smart Citations